3D echocardiography in mitral valve prolapse - Mantegazza, Valentina; Gripari, Paola; Tamborini, Gloria; Muratori, Manuela; Fusini, Laura; Ghulam Ali, Sarah; Garlaschè, Anna; Pepi, Mauro (Frontiers in Cardiovascular Medicine, 2023)
Mitral valve prolapse (MVP) is the leading cause of mitral valve surgery. Echocardiography is the principal imaging modality used to diagnose MVP, assess the mitral valve morphology and mitral annulus dynamics, and quantify mitral regurgitation. Three-dimensional (3D) echocardiographic (3DE) imaging represents a consistent innovation in cardiovascular ultrasound in the last decades, and it has been implemented in routine clinical practice for the evaluation of mitral valve diseases. The focus of this review is the role and the advantages of 3DE in the comprehensive evaluation of MVP, and intraoperative and intraprocedural monitoring.